1999
DOI: 10.1093/toxsci/48.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized uterotrophic effects of tamoxifen, toremifene, and estradiol in the ovariectomized Wistar (Han) rat

Abstract: The comparative uterotrophic responses of ovariectomized Wistar (Han) rats to tamoxifen, toremifene, and 17beta-estradiol have been determined over a period of 72 h. Uterine wet weight; luminal epithelial cell hypertrophy; and BrdU labeling index in the different tissue compartments of the uterus, and the immunohistochemical expression of nuclear estrogen receptor alpha (nERalpha), and nuclear progesterone receptor (nPR) were examined. Luminal epithelial cell hypertrophy was produced by all three compounds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…As monotherapy TOR has a significant and equivalent stimulatory effect on uterine epithelium as TAM. These monotherapy findings are consistent with published studies in this rat model [24][25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 93%
“…As monotherapy TOR has a significant and equivalent stimulatory effect on uterine epithelium as TAM. These monotherapy findings are consistent with published studies in this rat model [24][25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, a significant reduction in uterus weight was observed 3 weeks post-OVX, indicating a reduction in gonadal circulatiing hormones (Bekku and Yoshimura, 2005;Carthew et al, 1999;Skarda, 2002). Furthermore, Barker and Galea (2009) showed that at 3 weeks post-OVX there is a decline in b-estradiol levels in certain brain areas such as hippocampus, amygdala and prefrontal cortex (Barker and Galea, 2009).…”
Section: Influence Of Post-ovx Time Frame On Antidepressant-like Effesupporting
confidence: 61%
“…Previous studies have demonstrated that estrogens induce dramatic increases in uterine wet weight, luminal epithelial cell height, stromal thickness, and BrdU labeling (Carthew et al, 1999;Moggs et al, 2004b;Kwekel et al, 2005). In contrast, TCDD did not induce alterations in any of these histological or morphological endpoints (data not shown).…”
Section: Comparison Of Uterine Gene Expression Responses To Tcdd and Eementioning
confidence: 60%